A mid-Cretaceous female scale insect (Hemiptera: Sternorrhyncha: Coccomorpha) in Burmese amber - Poinar, George; Vega, Fernando E.; Schneider, Scott A. (Zootaxa, 2020)
A new genus and species of scale insect (Hemiptera: Coccomorpha) is described from a female specimen in mid-Cretaceous Burmese (Myanmar) amber. Fossil female scales are rare and the present species, described as Paleolepidotus macrocolus gen. et sp. n., has such an unusual assortment of morphological features that it could not be assigned to any particular extant or extinct family. The small, ferruginous specimen exhibits a series of long wax pencils that extend around the body, including the head. The antennae and legs are quite long compared to other extant and extinct scale fossils. Of special interest are the protruding eyes, and a conical-triangular rostrum arising from between the forelegs; the claws with bifid apices are also unique. The ovisac contains immature stages.